PENGARUH BAURAN PEMASARAN ( MARKETING MIX ) TERHADAP EFEKTIFITAS VOLUME PENJUALAN SAYURAN - I Ketut Artana; Sujianto Sujianto (Industri Inovatif : Jurnal Teknik Industri, 2011)
Being able to choose healthy food is the most important part of our latest lifestyle such as choosing hydroponic vegetables. PT Kusuma Satria Dinasasri Wisatajaya Batu is the main producer of pesticide free vegetables and fruit (hydroponic) which has promising prospect in its venture unit. Therefore we should organize reviewing toward effectiveness of sales volume. Within marketing there is a mix (marketing mix) which is part of marketing strategy consist of product, price, promotion, and distribution (place) within its marketing plan.To answer those questions author would like to offer hypothesis as follows: Sales Volume Effectiveness for Hydroponic Vegetables Affected by Marketing Mix at PT. Kusuma Dinasaari Wisatajaya Batu. Study method used in this paper is Descriptive Statistic Analysis and Multiple Linear Regression Analysis.Based on the method used in this study it is known that marketing mix implemented by PT. Kusuma Satria Dinasasri Wisatajaya Batu is quite effective, this is showed by each value of independent variables regression coefficient that is production cost (X1) 0,596, price pricing (X2) 10291,265; promotion cost (X3) 9,668 and distribution cost (X4) 3,358. It means that chosen variables has significant affect toward sales volume